Urban re-vision: Philippi market space - Motene, Katlego (School of Architecture, Planning and Geomatics, 2016)
This thesis investigates a link between food security and rural to urban migration in the city of Cape Town. Philippi as a Gateway to the City of Cape Town for many people migrating from rural South Africa, especially people from the Eastern Cape is therefore a natural site for the investigation. The point of departure is that the city is defined in relation to the landscape [agriculture being the generator of this landscape]. My observations are that when migrants come from rural settlement, where land is a primary source of food, through farming at household/community/commercial level, they abandon the embodied knowledge of how to produce a livelihood from the land as this knowledge is perceived to be of little value in the city. The aim of this thesis is to propose an architecture that allows the spatial practice of the migrant, as it relates to food production, to become visible as a function of the city.